German Chancellor, Angela Merkel, visits ILRI - International Livestock Research Institute (International Livestock Research Institute, 2011)
Through photographs and quotations, this film highlights the visit by Angela Merkel, the Chancellor of Germany, to the Nairobi headquarters of the International Livestock Research Institute (ILRI) on 12 July 2011.